2012
DOI: 10.1111/j.1365-2400.2011.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumstantial evidence of gibel carp, Carassius gibelio, reproductive competition exerted on native fish species in a mesotrophic reservoir

Abstract: Gibel carp, Carassius gibelio (Bloch), impacts on native fish species have been reported but little studied despite a long history of introductions in Europe. This species is able to reproduce gynogenetically, which involves the use of sperm from males of other species to activate egg development, so reproductive competition is a likely but virtually unstudied impact of gibel carp on native fishes. This study evaluates the impact of introduced C. gibelio on the population biology of native fishes over a 6‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 44 publications
1
46
0
1
Order By: Relevance
“…It is an omnivorous fish (Kottelat and Freyhöf, 2007), reproduces gynogenetically and has extensive tolerance to different environmental conditions (Ekmekçi, 2013). The reason for the intense reproductive success of introduced C. gibelio is its capacity for gynogenetic reproduction, whereby females are able to use sperm of other cyprinid fishes and salmonids to fertilize their eggs (Penaz et al, 1979;Tarkan et al, 2012). Consequently, this species easily becomes a dominant species in stagnant and slow running waters (Tsoumani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is an omnivorous fish (Kottelat and Freyhöf, 2007), reproduces gynogenetically and has extensive tolerance to different environmental conditions (Ekmekçi, 2013). The reason for the intense reproductive success of introduced C. gibelio is its capacity for gynogenetic reproduction, whereby females are able to use sperm of other cyprinid fishes and salmonids to fertilize their eggs (Penaz et al, 1979;Tarkan et al, 2012). Consequently, this species easily becomes a dominant species in stagnant and slow running waters (Tsoumani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This has been the case for the gibel carp in Turkey (Aydın et al, 2011;Tarkan et al, 2012b), and was demonstrated in a large-scale study of water bodies of the Great Lakes Region (USA), which indicated that reservoirs were more prone to invasion compared to neighboring natural lakes (Johnson et al, 2008). At the same time, propagule pressure appears to be the most reasonable explanation for the link between reservoirs and nonnative species.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have reported that the establishment success of introduced species into reservoirs may be high not only compared to natural lakes but also to water courses (Moyle and Light, 1996;Kolar and Lodge, 2002;Han et al, 2008;Aydın et al, 2011;Tarkan et al, 2012b). This has been the case for the gibel carp in Turkey (Aydın et al, 2011;Tarkan et al, 2012b), and was demonstrated in a large-scale study of water bodies of the Great Lakes Region (USA), which indicated that reservoirs were more prone to invasion compared to neighboring natural lakes (Johnson et al, 2008).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations